2016
DOI: 10.5468/ogs.2016.59.6.519
|View full text |Cite
|
Sign up to set email alerts
|

Recent trends in contraceptive use among Korean adolescents: Results from a nationwide survey from year 2013 to 2015

Abstract: ObjectiveThis study was aimed to evaluate the recent trends in contraceptive use among Korean adolescents.MethodsData reviewed were from the 2013–2015 Korean Youth Risk Behavior Web-based Survey, which is a stratified, multistage-sampling designed online-based research project performed annually by the Korean government to ensure a nationally representative sample of Korean adolescence. Eight questions related to the topic of contraception were reviewed for the outcome variables.ResultsA total of 212,538 adole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…According to a recent study conducted in Korea, the total percentage of adolescents who were found to be sexually active ranged from 5.0% to 5.3% [ 15 ]. The study also noted that the mean age for Koreans’ first sexual experience was between the ages of 12.8 and 13.2, which remained constant over the three-year period of the study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to a recent study conducted in Korea, the total percentage of adolescents who were found to be sexually active ranged from 5.0% to 5.3% [ 15 ]. The study also noted that the mean age for Koreans’ first sexual experience was between the ages of 12.8 and 13.2, which remained constant over the three-year period of the study.…”
Section: Discussionmentioning
confidence: 99%
“…The study also noted that the mean age for Koreans’ first sexual experience was between the ages of 12.8 and 13.2, which remained constant over the three-year period of the study. Lastly, among sexually active Korean female participants, 0.2% were reported to have experienced pregnancy, most of whom (66.1% to 73.6%) had undergone an induced abortion [ 15 ]. Hence, sexual health education is very important in helping to raise the age at which sexual behavior begins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A web-based study with Korean adolescents reported that 43.5%–53.3% of participants claimed they had never used contraception, although this rate is decreasing. 8 Trends in the use of contraceptives have revealed that condoms and the withdrawal method are the most frequently used methods in Korea, 8 9 and the proportion of participants using combined oral contraceptives (COCs) is lower (less than 3%) than that in other countries, such as the United Kingdom (21.6%), Canada (16.3%), and the United States (13.4%). 9 10 …”
Section: Introductionmentioning
confidence: 99%